Evaluation of snow storage in Western Siberia based on the land-surface model SPONSOR simulation using reanalysis data - D. V. Turkov; V. S. Sokratov; T. B. Titkova (Лëд и снег)
Obtaining of reliable information about the characteristics of snow cover with high spatial and temporal resolution for large areas of Northern Eurasia, with rare or absent network of ground-based observations stations is an important and urgent task. Currently estimation of the value of the snow water equivalent (SWE) and the snow depth have a large degree of uncertainty, especially if we are moving from data at the point of observation stations to distributed space values. In this article, the simulations of SWE and the snow depth using Land-Surface Model (LSM) SPONSOR with input meteorological data taken from the ECMWF ERAInterim reanalysis was performed for Western Siberia for the period from 1979 to 2013. Fields of SWE and of the snow depth with high spatial and temporal resolution corresponding to the resolution of meteorological data of the ECMWF ERA-Interim reanalysis (time step of 6 hours, the grid resolution of 0.75° × 0.75° in latitude and longitude) were obtained. For the entire period SWE data were compared with observations, as simulated using the model and taken directly from the reanalysis ERA-Interim at points corresponding of observation stations. Also comparison of observations and satellite data of SWE for points of observation stations was performed. Correlation coefficients between observations and model and satellite data for SWE and the snow depth were calculated for the period from 1979 to 2013. These correlation coefficients between observations and results of simulations using LSM SPONSOR for SWE, and especially for the snow depth are the best of all methods. Maps with high spatial resolution for SWE, obtained by different methods, were constructed for February averaged. Comparing of constructed maps shows significant uncertainty of the SWE fields, besides field’s distortions are not evenly distributed across the region. It appears that no one of these methods currently can be used as a reference (unique) to determine SWE in the absence of data of ground-based observations. Overall, model simulations using LSM SPONSOR somewhat overstate SWE, however, this overestimation is not more than 10–20% for most part of the territory, except in the South. Model data are reasonably well reproduce SWE for Central, Eastern and, most probably, for Northern parts of the region, differing from a real at 10–15%. Data from used satellite archive a few underestimate of SWE. SWE data taken directly from the reanalysis ERA-Interim, give large distortions of the SWE field: these values for Northern parts of the region, are likely greatly underestimated, and for Western and Eastern parts of the region – inflated. It is shown that in general, the method of simulation of snow cover characteristics using LSM SPONSOR with input data taken from the ECMWF ERA-Interim reanalysis gives good results for the region of Western Siberia.